Cross-Sample Comparisons and External Validity - Krupnikov, Yanna; Levine, Adam Seth (Journal of experimental political science, 2014)
Experimentation is an increasingly popular method among political scientists. While experiments are highly advantageous for creating internally valid conclusions, they are often criticized for being low on external validity. Critical to questions of external validity are the types of subjects who participate in a given experiment, with scholars typically arguing that samples of adults are more externally valid then student samples. Despite the vociferousness of such arguments, these claims have received little empirical treatment. In this paper we empirically test for key differences between student and adult samples by conducting four parallel experiments on each of the three samples commonly used by political scientists. We find that our student and diverse, national adult sample behave consistently and in line with theoretical predictions once relevant moderators are taken into account. The same is not true for our adult convenience sample.